2005
DOI: 10.1093/humrep/deh558
|View full text |Cite
|
Sign up to set email alerts
|

Partial deletions in the AZFc region of the Y chromosome occur in men with impaired as well as normal spermatogenesis

Abstract: BACKGROUND: Partial deletions of the AZFc region of the Y chromosome were reported to be a significant risk factor for oligo-/azoospermia. In this study, we assessed the occurrence and frequency of partial AZFc microdeletions in patients with spermatogenic failure and in controls with normal spermatogenesis. METHODS: In a retrospective study design, gr/gr, b1/b3 and b2/b3 deletions were analysed by multiplex PCR in 170 men with normal spermatogenesis and 348 men with non-obstructive oligo-/azoospermia. RESULTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
97
4
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(113 citation statements)
references
References 29 publications
9
97
4
3
Order By: Relevance
“…However, several groups evaluated these microdeletions in infertile men in order to illustrate their close relationship with infertility. Other studies reported significant correlations of gr/gr deletions (15)(16)(17) and insignificant associations of AZFc partial deletions with infertility in men (18)(19)(20)(21)(22). However, there are several factors that affect these results, such as demographic variations, differences in patient selection values, AZF in variable deletion regions, applying different STS markers, and environmental effects, and also the classification method used to define oligospermia with different amount of sperms varied, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, several groups evaluated these microdeletions in infertile men in order to illustrate their close relationship with infertility. Other studies reported significant correlations of gr/gr deletions (15)(16)(17) and insignificant associations of AZFc partial deletions with infertility in men (18)(19)(20)(21)(22). However, there are several factors that affect these results, such as demographic variations, differences in patient selection values, AZF in variable deletion regions, applying different STS markers, and environmental effects, and also the classification method used to define oligospermia with different amount of sperms varied, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the loss of specific AZFc STS was described, permitting the rapid and simple detection of AZFc partial deletion [3,5]. Several studies using this technique had previously been published [12,[25][26][27][28]. Nevertheless, duplication or deletion followed by duplication, as already described [5], cannot be detected by this technique used alone.…”
Section: Choice Of the Q-pcr Techniquementioning
confidence: 97%
“…The effect of AZFc microrearrangements on male fertility, in particular partial deletions, is still under discussion. Indeed, partial deletions have mainly been detected in infertile men, but several papers indicated that they were also found in fertile control men [5,[10][11][12][26][27][28]. Moreover, differences have been made between the incidence of "gr-gr" deletion and "b2-b3" deletion.…”
Section: Validation Of Q-pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…While in some studies the frequency of AZFc subdeletions (mainly the gr/gr) is higher in infertile men as compared to fertile controls [5,11,[20][21][22]; others have failed to confirm this association [23,24]. Based on four meta-analysis studies and a large population study involving >20,000 individuals it appears that the gr/gr deletion is a risk factor for male infertility [13,20,21,25,26]; the odds ratio is estimated to be 1.4-2.4 [5,20,21,25,26].…”
Section: Introductionmentioning
confidence: 99%